The influence of motivation and workload on the performance of outsourced nurses - Yolanda Erdiansari; Harries Madiistriyatno; Aswin Naldi Sahim (Privietlab, 2026)
This study aimed to analyze the effects of work motivation and workload on the performance of nurses outsourced by PT Alametric Teknologi Asia. The performance of outsourced nurses plays an important role in maintaining the quality of healthcare services provided at partner facilities. This study employed a quantitative approach with an associative design. Primary data were collected through questionnaires completed by 92 active outsourced nurses. The research instrument was evaluated through validity and reliability tests, and the regression model was assessed using normality, multicollinearity, and heteroscedasticity tests. Multiple linear regression analysis was used to examine the partial and simultaneous effects of the independent variables. The results showed that work motivation had a positive and statistically significant effect on the performance of outsourced nurses, whereas workload had a significant negative effect. Simultaneously, work motivation and workload had statistically significant effects on performance. The coefficient of determination showed an R Square value of 0.749, indicating that both variables explained 74.9% of the variation in the performance of outsourced nurses, while the remaining 25.1% was influenced by other factors outside the research model. These findings suggest that PT Alametric Teknologi Asia and its partner hospitals should strengthen employee motivation through fair rewards, recognition, professional development, and supportive supervision while maintaining proportional workload distribution, adequate staffing, and effective work scheduling.